2017
DOI: 10.1002/cncr.31170
|View full text |Cite
|
Sign up to set email alerts
|

Impact of latency time on survival for adolescents and young adults with a second primary malignancy

Abstract: Most AYAs who develop an SPM do so within 1 to 5 years of their primary cancer diagnosis, and they have an increased risk of death from cancer in comparison with AYAs with an SPM developing after longer survivorship intervals. Cancer 2018;124:1260-8. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
4
13
1
Order By: Relevance
“…Keegan et al (30) found that a previous cancer history was associated with a worse prognosis in patients with Hodgkin lymphoma, sarcoma, or breast, thyroid, or testicular cancers. A similar finding was also reported by Chao et al (22); moreover, recently, Goldfarb et al (31) noted that a longer latency time (>5 years) suggested an overall increased risk of death. However, none of these studies enrolled patients with head and neck MEC.…”
Section: Figure 2 |supporting
confidence: 84%
“…Keegan et al (30) found that a previous cancer history was associated with a worse prognosis in patients with Hodgkin lymphoma, sarcoma, or breast, thyroid, or testicular cancers. A similar finding was also reported by Chao et al (22); moreover, recently, Goldfarb et al (31) noted that a longer latency time (>5 years) suggested an overall increased risk of death. However, none of these studies enrolled patients with head and neck MEC.…”
Section: Figure 2 |supporting
confidence: 84%
“…19 Survivors of pediatric malignancies in the Childhood Cancer Survivor Study who previously were treated with abdominal radiation experienced an 11-fold increased risk of gastrointestinal SMNs. 11 A shorter latency time of within 1 to 5 years between the first cancer diagnosis and the SMN demonstrates an increased risk of death compared with a longer latency interval. 10 The British Childhood Cancer Survivor Study reported a cumulative incidence of CRC by age 50 years of 1.4% (95% CI, 0.7%-2.6%) for survivors treated with abdominopelvic irradiation, similar to rates observed in individuals with ≥2 first-degree relatives diagnosed with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…10 Latency time from initial diagnosis to the diagnosis of an SMN also has been shown to be a factor in survival outcomes. 11 A shorter latency time of within 1 to 5 years between the first cancer diagnosis and the SMN demonstrates an increased risk of death compared with a longer latency interval. Specifically, a colon SMN occurring within 5 years conferred a 9-fold increased risk of death compared with one with a latency period of >6 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations